TRANSFORMASI PENYELENGGARAAN PEMERINTAHAN DESA - Gregorius Sahdan (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
Village political authority to manage its authority has been eroded by the government through various sectoral ministry policies that are anti-village. The village has lost its authority as the subject of village administration. The central government places village administration as "scientific", through technocratization, namely applying applications that mislead villages. Villages are not managed politically, but technocratically which causes village democracy to not work. The state has even carried out neo-corporatism over villages with the aim that village transformation is more directed towards realizing the interests of the state, not the interests of the community. The transformation has strengthened the involution and formalism of village democracy, also causing village administration to return to the state-led government model or government run by the state, on state instructions, not based on community initiatives. The emergence of various government regulations such as Permendes No. 21 of 2020 concerning Guidelines for Implementing Village Development and Empowering Village Communities, not only makes villages more technocratic, but also kills village democracy, as mandated by Law No. 6 of 2014 concerning Villages.